ANALISIS KEPUASAN PENGGUNA TERHADAP SISTEM INFORMASI AKADEMIK - Safta Hastini; Dendi Irawan; Asnurul Isroqmi; Enggi Ardius (Yayasan Pendidikan Cahaya Budaya Indonesia, 2026)
This study was conducted to assess the level of usability and user satisfaction with the Academic Information System of Universitas PGRI Palembang. The evaluation employed the WebQual 4.0 method and was based on survey responses collected from students, lecturers, and staff who actively use the system. The results show that both usability and user satisfaction scored above 75%, indicating that the system is considered easy to use, capable of presenting relevant information, and effective in supporting various academic activities such as course registration (KRS), grade access, and course data management. The research instruments were also proven valid and reliable, making them appropriate tools for assessing the quality of the system’s services. However, several indicators require improvement, particularly those related to interface design and user experience. The indicators for attractive appearance (X1.5) and positive user experience (X1.8) scored lower than others, suggesting the need for interface redesign and more user-friendly guidance materials. Regression analysis further indicates that usability has a significant influence on user satisfaction, meaning that enhancements in navigation, interface consistency, and ease of access will directly contribute to higher satisfaction levels. Overall, this study provides a comprehensive overview of the quality of the Academic Information System and serves as an essential foundation for the development of a system that is more responsive, efficient, and adaptive to the needs of the academic community